A crise financeira e a política monetária no Brasil - Espindola, Ricardo Molari (2015)
The financial crisis that began in 2007 generated a major recession in the United States and affected the global economy with disastrous consequences for the growth and the rate of unemployment in several countries. The major Central Banks of the world have to give greater importance to policies that ensure financial stability. There is a consensus regarding the need for advanced regulatory and prudential measures capable of reducing the financial risks. However, there are differences in the use of the basic interest rate, not only as a necessary tool to ensure price stability, but also to ensure financial stability and prevent the formation of financial bubbles. In the last twenty years, Brazil has experienced a period of great expansion of its credit market, fruit of the economical and financial establishments. The Central Bank of Brazil had a successful performance during the crisis and demonstrated its ability in using instruments of monetary politics and prudential measures in a complementary manner. Over the past four years, the macroeconomic conditions have deteriorated and Brazil has gone through a period of low growth, a level of inflation that reaches its target ceiling and a rise in national debt. While macro-prudential policies were able to prevent the formation of financial bubbles, the fiscal and monetary policies were far too expansionary. In this period there was a weakening in the reaction function of the Central Bank, which has failed to comply with the principle of Taylor.